(3GdaUd aj Gdedd hGdfMds - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3CHh eMeO PgHJ GdeYJRdg hLge Hf UahGf Cf Gddg JYGdi dGjQi ai GdBNQI hbO QhjfG gPG Gdbhd Yf eLGgO hGdMSf GdHUQi s
(3BNQgG (B:s
(3heG cGf dge GdMjQI hCeG GdMSf aEf QShd Gddg Udi Gddg Ydjg hSde HYK Edjge s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B319s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds